An Organodiselenide Comediator to Facilitate Sulfur Redox Kinetics in Lithium–Sulfur Batteries with Encapsulating Lithium Polysulfide Electrolyte - Liu, Yiran; Zhao, Meng; Hou, Li‐Peng; Li, Zheng; Bi, Chen‐Xi; Chen, Zi‐Xian; Cheng, Qian; Zhang, Xue‐Qiang; Li, Bo‐Quan; Kaskel, Stefan; Huang, Jia‐Qi (Angewandte Chemie International Edition, 2023)
Lithium–sulfur (Li–S) batteries are regarded as promising high‐energy‐density energy storage devices. However, the cycling stability of Li–S batteries is restricted by the parasitic reactions between Li metal anodes and soluble lithium polysulfides (LiPSs). Encapsulating LiPS electrolyte (EPSE) can efficiently suppress the parasitic reactions but inevitably sacrifices the cathode sulfur redox kinetics. To address the above dilemma, a redox comediation strategy for EPSE is proposed to realize high‐energy‐density and long‐cycling Li–S batteries. Concretely, dimethyl diselenide (DMDSe) is employed as an efficient redox comediator to facilitate the sulfur redox kinetics in Li–S batteries with EPSE. DMDSe enhances the liquid–liquid and liquid–solid conversion kinetics of LiPS in EPSE while maintains the ability to alleviate the anode parasitic reactions from LiPSs. Consequently, a Li–S pouch cell with a high energy density of 359 Wh kg−1 at cell level and stable 37 cycles is realized. This work provides an effective redox comediation strategy for EPSE to simultaneously achieve high energy density and long cycling stability in Li–S batteries and inspires rational integration of multi‐strategies for practical working batteries. A redox comediation strategy is proposed for promoting the cathode redox kinetics and simultaneously retaining the anode protection capability of lithium–sulfur batteries using encapsulating lithium polysulfide electrolyte. A 1.5 Ah lithium–sulfur pouch cell realizes a high initial energy density of 359 Wh kg−1 and 37 stable cycles following the above strategy.